Application of A* Algorithm as a Solution for Finding the Shortest Route - Sunjana (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The application of the path finding algorithm is one way to solve various problems related to the search for the optimal route without obstacles or obstacles. To be able to provide solutions related to the optimal route problems, an algorithm can be used, namely the A * algorithm. A * is a route search algorithm that is often used to get the optimal route. By using the A * algorithm, the optimal route finding problem solving can be done quickly and easily. Algorithm A * can not only find one or two solutions, but provides the best solution and the optimal route. The simulation was carried out using the Visual Basic programming language. The purpose of this simulation is to find out how the A * algorithm works in the optimal route search, which is assumed to be the condition of someone looking for a route in a road condition that tends to be congested..